Characterization and identification of SFDC‐1, a novel AmpC‐type β‐lactamase in Serratia fonticola. (16th July 2021) - Dong, Xu; Zhang, Peiyao; Zhou, Kexin; Liang, Jialei; Li, Qiaoling; Zhang, Xueya; Zhou, Danying; Lu, Wei; Sun, Zhewei; Liu, Hongmao; Lu, Junwan; Lin, Xi; et al.
Summary: The clinical and environmental infections caused by AmpC β‐lactamases have been increasingly reported recently. In this study, we characterize the novel chromosome‐encoded AmpC β‐lactamase SFDC‐1 identified in Serratia fonticola strain R28, which was isolated from a rabbit raised on a farm in southern China. SFDC‐1 shared the highest amino acid identity of 79.6% with the functionally characterized AmpC β‐lactamase gene bla YRC‐1, although it had highly homologous functionally uncharacterized relatives in the same species from different sources, including some of the clinical significance. The cloned bla SFDC‐1 exhibited resistance to a broad spectrum of β‐lactam antibiotics, including most cephalosporins with the highest resistance to ampicillin, cefazolin and ceftazidime, with increased MIC levels ≥128‐fold compared with the control strains. The purified SFDC‐1 showed catalytic activities against β‐lactams with the highest catalytic activity to cefazolin. The genetic context of bla SFDC‐1 and its relatives was conserved in the chromosome, and no mobile genetic elements were found surrounding them.